Modified STEMI protocol for PPCI during COVID-19 Pandemic: Does it prolong Door-To-Balloon performance? - Putranto, Astri Yuniarsih; Putra, Teuku Muhammad Haykal; Soedarsono, Wahyu Aditya (Jurnal Kardiologi Indonesia, 2025)
In “Modified STEMI protocol for PPCI during COVID-19 Pandemic: Does it prolong Door-To-Balloon performance?” (Indonesian Journal of Cardiology, 44(3), 103-10. https://doi.org/10.30701/ijc.1325), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1325. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1325